OP0302 Moderate to High Disease Activity in Psoriatic Arthritis is Associated with Elevated Total Cholesterol and Triglycerides. (23rd January 2014) - Labitigan, M.; Shrestha, A.; Jordan, N.; Reed, G.; Magner, R.; Bahce-Altuntas, A.; Broder, A.
Abstract : Background: Psoriatic arthritis (PsA) is associated with a higher frequency of abnormal lipids and obesity compared with healthy controls and rheumatoid arthritis. There is also an increased risk of developing PsA in obese individuals, perhaps related to the inflammatory milieu provided by excess adiposity. It is also known that inflammatory cytokines contribute to derangements in lipid metabolism. However, the relationship between disease activity and lipid profiles in PsA is not well studied. Objectives: To assess the cross-sectional relationship between PsA disease activity and lipid profiles in the Consortium of Rheumatology Researchers of North America (CORRONA) Registry. Methods: We analyzed PsA patients followed in CORRONA between 6/2008 and 10/2012 with complete data for lipids and disease activity. Moderate to high disease activity was defined as CDAI>10 and/or presence of enthesitis/dactylitis. Abnormal lipids were defined as: total cholesterol (TC)>200 mg/dl (5.17 mmol/L), High Density Lipoprotein (HDL)<40 mg/dl (1.0 mmol/L, men), HDL<50 mg/dl (1.3 mmol/L, women), Low Density Lipoprotein (LDL)>100 mg/dl (2.59 mmol/L), Triglycerides (TG)>150 mg/dl (1.7 mmol/L), and atherogenic ratio (TC/HDL) >5. Models were adjusted for gender, duration of PsA, mHAQ, disease-related medication use, smoking, body mass index (BMI), diabetes (DM), use of cholesterol medications and fish oil. Results: Of the 725 PsA patients included in this study, 284 (39%) had moderate to high disease activity. Compared to the low disease activity group, the moderate to high disease activity group had a higher proportion of women (57% vs 46%, p=0.006) and smokers (12.7% vs 7.7%, p=0.029), higher log ESR (2.44 vs 2.13, p=0.003) and log CRP (1.63 vs 1.31, p=0.002), and shorter disease duration (mean 8.7 vs 11.2 years, p=0.001). Those with moderate to high disease activity were more likely to be prescribed prednisone (13% vs 4.5%, p<0.001) and non-biologic DMARDs (63% vs 51%, p=0.002), but were less likely to be prescribed TNF inhibitors (57% vs 66%, p=0.015). Mean BMI in moderate to high and low groups were 31.7kg/m2 and 30.6kg/m2, respectively, p=0.02. There were no differences between age, rate of DM, frequency of cholesterol lowering medications, and fish oil supplementation. Moderate to high disease activity was associated with higher odds of TC>200 mg/dl, OR 1.6 (1.1, 2.2 95%CI), p=0.010, and higher odds of TG>150 mg/dl, OR 1.6 (1.2, 2.3 95% CI), p=0.005. Enthesitis/dactylitis was positively associated with TC>200 mg/dl, OR 1.6 (1.1, 2.5), p=0.02. There was no significant association found between disease activity and other lipid measures in the moderate to high disease vs low disease groups. Conclusions: Moderate to high disease activity in PsA is associated with increased levels of total cholesterol and triglycerides, suggesting a commonality between PsA disease mechanisms and lipid metabolism that deserves further exploration. The implications of this association for cardiovascular disease in PsA need to be studied further. Disclosure of Interest: None Declared